Reinventing the future: a study of the organizational mind - Ramos, Isabel (2006)
This paper describes the concept of the self- and metarepresentation capabilities of the organization, a constituent of what we call the organizational mind. Our claim is that these capabilities are responsible for the emergence of a collective self that is of central importance in the formation of the organizational identity. These capabilities are relevant to the information systems field, as Information Technology applications play a central role in the support of those representational capabilities. The paper presents a summary of a theoretical perspective that supports a research project aimed at developing a framework to guide managers diagnosing identity dysfunctions resulting from impaired representational capabilities of the organization.